2022
DOI: 10.3390/ijerph19127244
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Korean Version of the Holistic Nursing Competence Scale

Abstract: This methodological study aimed to verify the validity and reliability of the Korean version of the Holistic Nursing Competence Scale (HNCS), which comprises five dimensions and 36 items. The English version of the HNCS was forward and backward translated and administered to 251 participants with more than a year of work experience in a general hospital. Data were analyzed using SPSS WIN 24.0(Chicago, USA), and AMOS program was used for confirmatory factor analysis. Additionally, the “Task Performance Evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The higher the score, the higher the nurses’ holistic nursing competence. Cronbach’s α of the tool was 0.96 in Seo et al’s [ 12 ] study, and that in this study was 0.96.…”
Section: Methodssupporting
confidence: 60%
See 2 more Smart Citations
“…The higher the score, the higher the nurses’ holistic nursing competence. Cronbach’s α of the tool was 0.96 in Seo et al’s [ 12 ] study, and that in this study was 0.96.…”
Section: Methodssupporting
confidence: 60%
“…Holistic nursing competence was measured using the Holistic Nursing Competence Scale developed by Takase and Teraoka [ 7 ] and translated into Korean by Seo et al [ 12 ]. This tool consists of 36 items measured on a 7-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 This indicates that as nurse executives gain more experience, they may become more willing to take on leadership roles. 37 Seo et al 38 highlighted that nursing competence increases with years of experience suggesting that as nurse executives gain more experience, they become more competent. However, Friedman et al 39 identified a gap between identity and reputation in nurse executive leadership, suggesting that self-awareness and personal development may also play a crucial role in leadership effectiveness, independent of experience.…”
Section: Discussionmentioning
confidence: 99%